Meningoencephalic Neurotoxoplasmosis. Entrance work as a corresponding member of the ecuadorian academy of medicine - Lazo Salazar, Ramon F. (Revista Universidad de Guayaquil, 2015)
Curretly it is remarkable the incidense of cerebral toxoplasmosis in immunocopromised or human immunodeficiency síndrome (AIDS) patients. In the etiologic diagnosis of cerebral toxoplasmosis newborn I have participad since 1965 and, with sudden apoplectic stroke, two months after a high fever, hepatalgia, jaundice and dark urine acolia. The November 2, 1994 originates, I request your attention, We practice immunological study for Toxoplasmosis, indirect imnunofluorescense, IFI is positive with IgG figures. 1:16000 and IgM. 1:8000. In brain CT hypodense area wide level capsular thalamus, some in the form of ring abscess possibility of evolution is observed. With the diagnosis of meningoencephalic neurotoxoplasmosis indicate the relevant treatment observes al 13 days improved very satisfactory. We report the developement, having, requested hospital discharge and tranfer family with persistent rain, caused pneumonia and outcome, this report constitutes an unpleasant experience for not being diagnosed early